Prevalence of Listeria monocytogenes in Retail Beef and Poultry - Rahmat Ali, Gulam Rusul; Ibrahim, Aziah; Abu Bakar, Fatimah (1991)
Preliminary studies on local and imported beef, minced beef, chicken pieces, minced chicken meat and internal organs of poultry from wet market sand supermarkets were carried out and analysed for the presence of Listeria monocytogenes.L. monocytogenes was isolated by direct plating on Palcam agar and with selective and cold enrichment at 37" and 4°Cin L-Palcamy enrichment broth. Whole chickens and the equipment used for processing of poultry were also swabbed and examined for the presence of the organism. L. monocytogenes was detected in 6/16imported and 3/6 local beef samples. Out of 16 poultry samples which were obtained from four different wet markets, six contained L. monocytogenes. Beef samples obtained from supermarkets were negative for L. monocytogenes but the organism was detected in three of four imported minced beef, and two of four local minced beef samplesL. monocytogenes was also detected in three of thefour chicken samples; two off ourminced samples and one off our organs which were obtained from supermarkets. Chicken carcasses from wet market A were negative for L. monocytogenes but this was not true for chicken carcasses from wet market B because 15 out of24 were positive for L. monocytogenes. No. L. monocytogenes was detected from the equipment in wet market A, but equipment in wet market B was positive for the organism. These results suggest that retailing meats which have been processed for many hours favour growth of L. monocytogenes and also enhance cross-contamination.